1990
DOI: 10.1007/bf02052319
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary resection for metastatic colon and upper rectum cancer

Abstract: The predictive value of the route of venous drainage on prognosis was investigated in a consecutive series of 44 patients who underwent curative resection of pulmonary metastases from colorectal carcinoma. The primary tumor was located in the colon in 14 patients and in the upper third of the rectum in 11 patients, thus indicating blood drainage directed toward the portal vein (Group I). In 10 and 9 cases, respectively, the initial growth was in the middle and lower thirds of the rectum with the venous outflow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 10 publications
1
16
1
Order By: Relevance
“…While cancer of the [8] 38.6 McAfee et al [ 11 ] 30.5 Marks et al [16] 41.2 Wright et al [21] 30 Morrow et al [22] 13 This study 23 colon metastasizes exclusively via the portal vein, metastases of rectal cancer can spread via the inferior vena cava, although our observations are in agreement with those ofScheel et al [13]: i.e. there are no statistically sig nificant differences between the two locations.…”
Section: Discussioncontrasting
confidence: 44%
“…While cancer of the [8] 38.6 McAfee et al [ 11 ] 30.5 Marks et al [16] 41.2 Wright et al [21] 30 Morrow et al [22] 13 This study 23 colon metastasizes exclusively via the portal vein, metastases of rectal cancer can spread via the inferior vena cava, although our observations are in agreement with those ofScheel et al [13]: i.e. there are no statistically sig nificant differences between the two locations.…”
Section: Discussioncontrasting
confidence: 44%
“…Although several reports have described skip metastasis from colon cancer bypassing the liver and spreading to the lungs and/or thyroid gland (1), the precise mechanism for this is unclear, and they are regarded as exceptional cases. In general, venous drainage is thought to be the decisive determinant for distant hematogenous tumor spread (5). There are several references to the anatomy of venous drainage in the rectum.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, rectal cancer is known to be more strongly associated with the presence of isolated pulmonary metastases than colon cancer (1). It has been suggested that this difference reflects the different routes of venous drainage in the colon and rectum, as venous drainage is thought to be the decisive determinant for distant hematogenous spread (5). Generally, blood from the colon is directed toward the liver via the portal vein, while blood from the rectum drains into the systemic circulation (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 The higher incidence of this isolated lung metastases in rectal compared to colonic carcinoma was attributed to the direct hematogenous spread into the systemic circulation via the inferior and middle rectal veins, bypassing the portal venous system. 3,7 However, colon cancer with isolated metastases not involving the liver is considered very rare with only a few reports mentioning the existence of such an entity. 3,4 Our study aims to review the incidence of isolated lung metastases in all patients with colorectal cancers and to identify clinical factors that could be associated with this phenomenon.…”
Section: Introductionmentioning
confidence: 98%